The Incidence of Winged Scapula after Thoracic Cancer Surgery: A Prospective Cohort Study - Teixeira, Luiz Felipe Nevola; Sandrin, Fabio; da Silva, Ruy Fernando Kuenzer Caetano; Petrella, Francesco; Bertolaccini, Luca; Simoncini, Maria Claudia; Spaggiari, Lorenzo (The Thoracic and Cardiovascular Surgeon, 2024)
Background Lung cancer is the leading cause of cancer-related deaths, and surgery is still the first treatment of choice in early and locally advanced cases. One of the iatrogenic complications is the serratus anterior palsy, which could lead to a winged scapula (WS). Unfortunately, the incidence of this deficit in thoracic surgery is unclear. Our primary aim was to determine the incidence of WS in lung cancer patients in a single-center experience.Methods We conducted a retrospective analysis of prospectively collected data with patients eligible for oncological thoracic surgery from March 2013 until January 2014. A physical evaluation of the WS was performed pre- and postoperatively, at the discharge and after 1 year of follow-up.Results A total of 485 patients were evaluated; 135 (27.8%) showed WS. Longer operative time (p < 0.0001), type of surgery (p < 0.0001), lymphadenectomy (p < 0.0001), and neoadjuvant treatment prior surgery (p = 0.0005) were significantly related to the WS injury. Multivariable analysis showed that type of surgery was significantly associated with WS (p < 0.0001). After 1 year, 41.6% still had WS.Conclusion The incidence of WS was similar to the literature. As WS incidence is underdiagnosed, assessment and correct education about possible deficits or impairments should be improved. Moreover, when a minimally invasive approach is not planned, it is a good clinical practice to discuss surgical strategies with surgeons to reduce this deficit.
Keywords: lung neoplasms; lung cancer; thoracic surgery; nervous system trauma; rehabilitation; physical therapy specialty